PRAKTIK KEBERLANJUTAN PADA MEREK TEKSTIL DAN FESYEN INDONESIA: RUPAHAUS DAN OSEM - Rahayu Budhi Handayani (Universitas Ciputra Surabaya, 2019)
The Study of Sustainability Practices in Indonesian Textile and Fashion Brands: Rupahaus and Osem describe how the principles of sustainability in fashion and textiles are practiced. Generally, environmentally friendly brands are often associated with the use of natural materials. Whereas in the production process of natural materials such as cotton also have a negative impact on the environment because of the need for the use of a lot of pesticides and fertilizers. Thus, the practice of sustainability in fashion and textiles needs to be seen from the production process, distribution process, consumption process, to final disposal. Using a qualitative descriptive approach, this paper further examines the existing sustainability practices of Indonesian fashion brands with purposive sampling on the Rupahaus and Osem